Because of Thursday - Polacco, Patricia (New York : Simon & Schuster Books for Young Readers, 2016)
"Annie Fetlock--born on Thursday, met the love of her life on Thursday, and when a special cat comes into her life on Thursday, she knows he has found the right home"--
"A Paula Wiseman book."
Ages 4-8.
Keywords: Days -- Fiction; Cats -- Fiction